The Effectiveness of Emotion-Focused Therapy on Improving Marital Intimacy and Marital Adjustment - Shafieefar , Elham; Zargham Hajebi, Majid; Tabarraei , Ramin (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to investigate the effectiveness of Emotion-Focused Therapy (EFT) in enhancing marital intimacy and marital adjustment among couples.Methods and Materials: This research utilized a quasi-experimental design with pretest–posttest and a control group, including a three-month follow-up. The statistical population consisted of couples who attended counseling centers in Qom in 2021. Using convenience sampling and based on sample size estimation via G*Power (effect size = 0.36, α = 0.05, power = 0.95), 48 individuals (24 couples) were selected and randomly assigned to experimental and control groups. The intervention group participated in eight weekly 90-minute group sessions of EFT based on the protocol by Leslie Greenberg and colleagues (2008; as cited in Fathi et al., 2021), while the control group received no intervention. Data were collected using the Bagarozzi Marital Intimacy Questionnaire (2001) and the Spanier Dyadic Adjustment Scale (1976). Data analysis was performed using 3×2 repeated measures ANOVA in SPSS version 26.Findings: Results showed a significant main effect of group on marital intimacy (F = 247.3, p < .05, η² = .662) and marital adjustment (F = 232.06, p < .05, η² = .89). The main effect of time (pretest, posttest, follow-up) was also significant for marital intimacy (F = 198.4, p < .05, η² = .686) and marital adjustment (F = 12.2, p < .05, η² = .31). Bonferroni test comparisons indicated significant increases from pretest to posttest and follow-up in both variables (p < .001).Conclusion: The findings suggest that EFT is an effective intervention for improving marital intimacy and marital adjustment, with effects sustained at follow-up, making it a promising approach to enhance relational functioning among couples.